TINJAUAN YURIDIS TENTANG PELAKSANAAN PERJANJIAN TANGGUNG JAWAB ANGGOTA KOPERASI DALAM MENGATASI KREDIT MACET (Studi Kasus PNM Mekaar Pasar Kemis, Kab. Tangerang) - Irwan Sapta Putra; Mohammad Hifni; Silvia Amanah (Gapenas Publisher, 2026)
The implementation of financing agreements at PNM Mekaar employs a joint liability system as a form of shared responsibility among group members. In practice, however, problems such as non-performing loans still arise, affecting the smooth payment of installments and impacting other group members. This study aims to analyze the implementation of cooperative member liability agreements at PNM Mekaar, the factors causing non-performing loans, and efforts to address them. This study employs an empirical legal research method with an empirical juridical approach. Data were collected through interviews, observations, and a literature review, and were subsequently analyzed qualitatively. The results of the study indicate that the implementation of financing agreements has been in accordance with applicable legal provisions. However, nonperforming loans were still found to be caused by internal factors—such as a decline in business income, health issues, and poor financial management—as well as external factors, including a lack of good faith on the part of members and changes of residence without prior notice. In addressing these issues, PNM Mekaar prioritizes communication, deliberation, and visits to members before implementing the joint liability system as stipulated in the agreement. Based on the research findings, the implementation of the joint liability agreement at PNM Mekaar has been carried out in accordance with legal provisions; however, its effectiveness is still influenced by members’ awareness and sense of responsibility in fulfilling their obligations.